Is Teacher Training Necessary for Medical Educators? - Lakhe, Gajal (Nepal Journal of Medical Sciences, 2025)
Teacher training is crucial for those involved in medical education. This field requires not only a deep understanding of the subject matter but also skills in teaching methodologies, effective communication, and assessment techniques. Well-structured training programs prepare educators to effectively implement active learning strategies, including problem-based learning and simulations. It fosters critical thinking and problem-solving skills amongst the learners. It also improves the capacity to create thorough assessment methods. Ultimately, investing in the development of faculty ensures that medical educators are well-prepared to shape skilled and empathetic future healthcare professionals.